2021
DOI: 10.1007/s00204-021-02987-4
|View full text |Cite
|
Sign up to set email alerts
|

The BH3 mimetic (±) gossypol induces ROS-independent apoptosis and mitochondrial dysfunction in human A375 melanoma cells in vitro

Abstract: A major challenge in current cancer therapy is still the treatment of metastatic melanomas of the skin. BH3 mimetics represent a novel group of substances inducing apoptosis. In this study, we investigated the cytotoxic effect of (±) gossypol (GP), a natural compound from cotton seed, on A375 melanoma cells and the underlying biochemical mechanisms. To prevent undesired side effects due to toxicity on normal (healthy) cells, concentrations only toxic for tumor cells have been elaborated. Viability assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
2
11
1
Order By: Relevance
“…The results are shown in Figure 4A,B. After RAW264.7 cells were exposed to 20, 40, 60, and 80 μM DFC for 6 h as the concentration of the virus gradually increased, the green fluorescent signal decreased significantly, indicating the loss of MMP 29 . When it reaches 80 μM, the green fluorescence almost disappears.…”
Section: Resultsmentioning
confidence: 97%
“…The results are shown in Figure 4A,B. After RAW264.7 cells were exposed to 20, 40, 60, and 80 μM DFC for 6 h as the concentration of the virus gradually increased, the green fluorescent signal decreased significantly, indicating the loss of MMP 29 . When it reaches 80 μM, the green fluorescence almost disappears.…”
Section: Resultsmentioning
confidence: 97%
“…GAA is a crystallized form of gossypol ( Figure 4 A); it is the most biologically active form of this phenol [ 17 ]. Previous studies have shown that gossypol induces cell death in cancer cells [ 18 , 19 ] and germline stem cells [ 20 ]; hence we used primary neonatal rat cardiomyocytes cultured in vitro and treated with GAA (20 and 50 μM) to assess the induction of cell death via flow cytometry analysis with Annexin V-FITC and PI for apoptosis and necrosis detection, respectively ( Figure 4 B). GAA did not cause significant necrosis (Q1), late apoptosis (Q2), or early apoptosis (Q3) relative to the positive control, i.e., 20-μM H 2 O 2 ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…GAA is a crystallized form of gossypol (Figure 4A); it is the most biologically active form of this phenol [17]. Previous studies have shown that gossypol induces cell death in cancer cells [18,19] and germline stem cells [20]; hence we used primary neonatal rat cardiomyocytes cultured in vitro and treated with GAA (20 and 50 μM) to assess to the ferroptosis inhibitors, GAA significantly improved ferroptotic cell death in RSL3and Fe-SP-treated cardiomyocytes. To confirm the effect of GAA on ferroptosis, we used the lipid ROS probe C11 BODIPY 581/591 and performed confocal microscopy observations.…”
Section: Effects Of Gaa On Ferroptosis-induced Neonatal Rat Myocardial Cell Deathmentioning
confidence: 99%
“…HPLC was performed on a Supelco pKb 100 (250 × 4.6 mm) column with a mobile phase consisting of AcN/water/trifluoroacetic acid (90/10/0.1, v/v/v) at a flow rate of 1.0 ml/min (0–10 min) and UV detection at 367 nm. Retention time of GP was around 5 min (Haasler et al 2021 ). Only intracellular GP and not its metabolites were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was described that GP acetate at high concentrations led to an autophagic block in the human non-small-cell lung cancer cell line A549 (Cai et al 2022 ). Previously, we demonstrated that GP exhibited a selective toxicity on A375 melanoma cells via mitochondrial dysfunction finally resulting in apoptotic cell death (Haasler et al 2021 ). In this in vitro study, we focused on the effect of GP on the NMSC cell line SCL-1 which is a model of cSCC showing malignant growth characteristics and an invasive capacity in vivo (Boukamp et al 1982 ).…”
Section: Introductionmentioning
confidence: 99%